Transcriptome profile of the human endothelial cell response to high- and low-density infections of Candida albicans - Chong, Pei Pei; Rozita, Rosli; Seow, Heng Fong; Lim, Crystale Siew Ying; Tan, Hui Yin (Elsevier, 2010)
Background: Candida albicans morphology switching and quorum-sensing are important factors for pathogenicity and virulence in persons with a compromised or deficient immune system. This study investigates the in vitro response of human umbilical vein endothelial cells (HUVECs) to infections with low and high densities of C. albicans. We hypothesize that higher cell densities of C. albicans yeast-form cells (blastospores), are more detrimental to HUVECs than lower cell densities of hyphal forms.